2019
DOI: 10.3892/ol.2019.10855
|View full text |Cite
|
Sign up to set email alerts
|

TIM‑3 expression and its association with overall survival in primary osteosarcoma

Abstract: T-cell immunoglobulin and mucin domaincontaining-3 (TIM-3) performs a critical function in immune tolerance by suppressing the activation and proliferation of T cells. TIM-3 serves an important role in tumor progression in a number of carcinomas, including non-small cell lung cancer, hepatitis B virus-associated hepatocellular carcinoma, Langerhans cell sarcoma, head and neck cancer and follicular B cell non-Hodgkin lymphoma. The aim of the present study was to evaluate the possible association of TIM-3 with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…A total of 3,072 patients, ranging from 30 to 587 patients per study, were involved in our meta-analysis. Among all eligible studies, 13 studies focused on the TIM-3 expression on tumor cells ( 10 14 , 28 33 , 36 , 39 ), six studies centered on the TIM-3 expression on TILs ( 9 , 34 , 35 , 37 , 38 , 40 ), one study combined the TIM-3 expression on tumor cells and TILs ( 41 ), and one study analyzed the TIM-3 expression on tumor cells and TILs separately ( 42 ). All researches utilized the IHC techniques to detect the expression level of TIM-3.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3,072 patients, ranging from 30 to 587 patients per study, were involved in our meta-analysis. Among all eligible studies, 13 studies focused on the TIM-3 expression on tumor cells ( 10 14 , 28 33 , 36 , 39 ), six studies centered on the TIM-3 expression on TILs ( 9 , 34 , 35 , 37 , 38 , 40 ), one study combined the TIM-3 expression on tumor cells and TILs ( 41 ), and one study analyzed the TIM-3 expression on tumor cells and TILs separately ( 42 ). All researches utilized the IHC techniques to detect the expression level of TIM-3.…”
Section: Resultsmentioning
confidence: 99%
“…Tim-3 by binding to its ligand Galectin-9 (Gal-9) could induce apoptosis and immune tolerance of T cells. In this study, Tim-3 was also found to be expressed in macrophages, NK cells, and other natural immune cells, which may play an important role in maintaining immune homeostasis [30]. Using Western blot assay, we detected high expression of Tim-3 protein in osteosarcoma tissues and cells., which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 53%
“…Tim-3 could induce macrophage M2 differentiation and aggravate podocyte damage to participate in the occurrence and development of the disease through NF-κB/TNF-α pathway in diabetic nephropathy [28,29]. In osteosarcoma, it has been documented that the expression of Tim-3 is signi cantly increased in tumor tissue [30], and the overexpression of Tim-3 could promote the occurrence and development of osteosarcoma. However, whether the overexpression of Tim-3 in osteosarcoma could also regulate the differentiation of tumor-associated macrophages and the underlying molecular mechanism of this regulation remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Knockout of IL-1R8 has been shown to restore NK cell antitumor function in MCA-induced sarcomas, implicating a role of IL-1R8 in sarcoma-mediated NK cell suppression [ 92 ]. Expression of other checkpoint molecules such as T-cell immunoglobulin and mucin domain-3 (TIM-3) ligands and NKp44-inhibiting proliferating cell nuclear antigen (PCNA) was also reported in sarcomas [ 45 , 139 ].…”
Section: Nk Cell Dysfunction In Sarcomasmentioning
confidence: 99%